2008
DOI: 10.1007/s00167-008-0635-6
|View full text |Cite
|
Sign up to set email alerts
|

Distal realignment and patellar autologous chondrocyte implantation: mid-term results in a selected population

Abstract: The aim of this prospective observational study was to assess the 3-year clinical outcome of distal realignment and membrane-seeded autologous chondrocyte implantation (MACI Ò ) in selected patients with patellofemoral malalignment and large, isolated, patellar cartilage lesions. Twelve patients (14 knees; 6 females, 6 males; mean age 31 years) with Fulkerson type II patellofemoral malalignment (lateralized and tilted patella) and Outerbridge grade III-IV isolated patellar cartilage lesions were treated. All h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 47 publications
2
71
0
Order By: Relevance
“…An expected decline in the KOOS sport and recreation subscale was seen from the point before surgery to 3-month follow-up because of the physical limitations imposed on patients at this early postoperative time to minimize the risk of early graft Composite score 3 mo 2.9 6 0. [17][18][19][20][21]29,30,36,48 Patients demonstrated a significant improvement over the postoperative timeline for the 6-minute walk test and active knee flexion and extension, with the primary improvement occurring between 3 and 12 months as expected. While the 6-minute walk test has been reported as a foundation for functional independence and an important component of many activities of normal daily living, 40 it may be argued that it is not a validated measure in MACI patients, nor is walking on level terrain at pace an activity that significantly troubles patients with patellofemoral symptoms.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…An expected decline in the KOOS sport and recreation subscale was seen from the point before surgery to 3-month follow-up because of the physical limitations imposed on patients at this early postoperative time to minimize the risk of early graft Composite score 3 mo 2.9 6 0. [17][18][19][20][21]29,30,36,48 Patients demonstrated a significant improvement over the postoperative timeline for the 6-minute walk test and active knee flexion and extension, with the primary improvement occurring between 3 and 12 months as expected. While the 6-minute walk test has been reported as a foundation for functional independence and an important component of many activities of normal daily living, 40 it may be argued that it is not a validated measure in MACI patients, nor is walking on level terrain at pace an activity that significantly troubles patients with patellofemoral symptoms.…”
Section: Discussionmentioning
confidence: 63%
“…17,33 Furthermore, of the aforementioned studies, only 4 appear to undertake some form of magnetic resonance imaging (MRI)-based assessment. 19,20,33,47 The aim of this study was to prospectively evaluate preand postoperative clinical and radiologic outcome in patients undergoing MACI to address isolated patellofemoral chondral lesions (patella or trochlea).…”
mentioning
confidence: 99%
“…In patients with lateral and distal patellar defects, anteromedialization led to 100% patient satisfaction with 87% good to excellent results, while patients with medial, proximal, or diffuse defects had only 43% good to excellent results (Pidoriano, Weinstein et al 1997). Excellent short-and mid-term outcomes have been demonstrated when distal patellofemoral realignment has been combined with ACI (Bentley, Biant et al 2003;Minas and Bryant 2005;Henderson and Lavigne 2006;Farr 2007;Gigante, Enea et al 2009;Gobbi, Kon et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…According to Pidoriano et al, anteromedialization of the tibial tubercle improves knee function and relieves anterior knee pain in 90 and 85 % of type I and II patellar cartilage lesions (inferior pole and lateral facet), respectively, with lower success rates for type III (medial facet, 56 %) and type IV defects (proximal pole or diffuse lesions, 20 %) [ 41 ]. Gigante et al also reported significant clinical improvement after 36 months of distal realignment and autologous chondrocyte implantation in treating large, isolated, patellar cartilage lesions associated with patellofemoral malalignment [ 42 ].…”
Section: Introductionmentioning
confidence: 95%